ACTIVITY OF MODERN POLITICAL PARTIES IN THE JAPANESE ELECTORAL SYSTEM (American Journal of Research in Humanities and Social Sciences, 2023)
This article discusses modern political parties in Japan and their activities. Also, politics of Japan are conducted in a framework of a dominant-party bicameral parliamentary constitutional monarchy, in which the Emperor is the head of state and the Prime Minister is the head of government and the head of the Cabinet, which directs the executive branch. Legislative power is vested in the National Diet, which consists of the House of Representatives and the House of Councillors. The House of Representatives has eighteen standing committees ranging in size from 20 to 50 members and The House of Councillors has sixteen ranging from 10 to 45 members.Judicial power is vested in the Supreme Court and lower courts, and sovereignty is vested in the people of Japan by the 1947 Constitution, which was written during the Occupation of Japan primarily by American officials and had replaced the previous Meiji Constitution. Japan is considered a constitutional monarchy with a system of civil law.